URBAN SPATIAL GROWTH AND LANDUSE CHANGE DETECTION ANALYSIS OF ALIGARH CITY, UTTAR PRADESH, INDIA USING HIGH RESOLUTION REMOTE SENSING DATA, GEOGRAPHICAL INFORMATION SYSTEM (GIS) AND GLOBAL POSITIONING SYSTEM (GPS) TECHNIQUES - Kumar, Virendra; Rathore, Vijay Kumar Singh (International Journal of Engineering Technologies and Management Research, 2016)
Use of High Resolution temporal satellite imageries and Geographical Information System (GIS) provide us present and past status of extensions and Landuse change in oukskirts of urban centres. The present paper is an attempt to analyze the temporal urban growth and landuse change of Aligarh city using Survey of India Topographical Map surveyed in 1971 and IKONOS satellite data of various time periods from 2004, 2009 and 2014. The result shows that in 1971 the urban built-up land of the city based on SOI Topographical Map was 2224.6555 hectare, based on interpretation of IKONOS satellite imagery of 2004, 2009 and 2014 , the urban built-up area of the city is 4724.7614 hectare in 2004, 5872.6774 hectare in 2009 and 7059.8875 hectare in 2014 respectively. This has increased to 2500.1059 hectare in a period of 33 years from 1971 to 2004 and in the period from 2004-2009 and 2009-2014 it has increased by 1148 hectare and 1187.211 hectare respectively. Agricultural land, Orchard/Plantations and water bodies to built-up (urban) has been calculated in GIS and it has been observed that there is a tremendous increase in the built-up urban area. The loss of prime arable land, orchard/plantation and water bodies has been converted in to built-up urban land. The digital database created for urban growth and landuse change of Aligarh city, Uttar Pradesh, India using multi-date data in Arc-GIS software would be very useful for urban development authorities, planners, decision makers for better landuse planning and management for proposed landuse programmes.